The Genetic Variability of Prolactin and Signal Transducers and Activators of Transcription 5A (STAT5A) Genes in Bali Cattle - Komang Alit Paramitasari; Cece Sumantri; . Jakaria (Faculty of Animal Science, Bogor Agricultural University, 2015)
The aim of this study was to identify the genetic variability of PRL and STAT5A genes in Bali cattle from Bali, West Nusa Tenggara (NTB), and South Sulawesi (SS) using PCR-RFLP method. A total of 262 Bali cattle were identified using RsaI (PRL) and AvaI (STAT5A) restriction enzymes. PRL gene exon 3, PRL gene exon 4, and STAT5A gene exon 7 amplifications resulted fragments with the lengths of 156 bp, 294 bp, 215 bp, respectively. Genotyping of PRL gene both at exon 3 and 4 produced three genotypes in Bali population and two genotypes in NTB and SS population. For the PRL gene, frequencies of A allele (exon 3) and G allele (exon 4) were dominant to the B allele (exon 3) and A allele (exon 4) across all populations. The results showed that STAT5A|AvaI loci had monomorphic C allele. Heterozygosity values were found low at both exons 3 and 4 of PRL gene in all population. Sequence analysis results of PRL gene both for exons 3 and 4 showed that there was a mutation between adenine (A) and guanine (G) bases in the RsaI recognized site, whereas in STAT5A gene we can confirm the existence of AvaI restriction site (C|CCGAG).Key words: bali cattle, genetic polymorphism, PCR-RFLP, prolactin gene, STAT5A gene